TorakochirurgiaUsefulness of scintigraphy in the diagnostics of patients after splenectomy: a case report - Wójcik, Norbert; Wójcik, Janusz; Grodzki, Tomasz; Kubisa, Bartosz; Pieróg, Jarosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
A case of a 31-year-old man with a suspicion of sarcoidosis or thoracic splenosis (TS) due to previous splenectomy is described. Sarcoi-dosis was confirmed by Daniels’s biopsy. Scintigraphy showed focuses of abdominal splenosis, lack of focuses of TS and confirmed usefulness when splenosis is suspected.